Pengaruh Pengawasan dan Pelatihan Terhadap Efektivitas Pelaksanaan Elektronik Manajemen Penyidikan (e-MP) Oleh Tim Penyidik Satuan Reskrim : Studi Pada Polres Belitung Timur - Hanafi, Muhammad Rochli; Prisgunanto, Ilham; Sinaga, Saut Panggabean (Prisani Cendekia, 2024)
One way to realize services in the field of law or police law enforcement is to use the electronic Investigation Management System (e-MP) approach. E-MP is an application that really helps members of the investigation from the leadership level to investigators and assistant investigators to be able to interact in working in an investigation management system. starting from the police report, the assignment of personnel in handling a case, until the case is handled which are all integrated with each other. The research method used in this research is a type of analytical observation research, which is a research approach in which the data collection is without any intervention in the population. This study aims to describe the effect of supervision and training on the effectiveness of the implementation of Investigation E-Management using a cross sectional research design, which is an approach used to observe variables through data collection only once, at one time or using an approach. The results showed that the existing supervision system at the East Belitung. Police was mostly in the very good category. This can be seen from the implementation of the effectiveness of the implementation of E-management of investigations mostly in the very effective category. The supervision system and training at East Belitung Police simultaneously have a significant effect on the effectiveness of the implementation of Investigation E-Management.